How the therapy for endometriosis affects the hormonal status in female infertility - N. Yu. Pedachenko; T. L. Shemelko; R. A. Tukhtarian (Kazimierz Wielki University, 2020)
Aim. To determine changes in the values of pituitary and ovarian hormones in women with endometriosis-associated infertility, as well as to evaluate the impact of endometriosis therapy on hormonal parameters Materials and Methods. Sixty-nine women with small-sized endometriomas with adenomyosis (target group) and 50 women with tubal infertility (controls) were examined. The values of pituitary (luteinizing and follicle-stimulating hormones, prolactin) and ovarian (estradiol, tubular antimullerian hormone) hormones were studied. The comparison of quantitative indicators between the studied groups of women was carried out using the Mann-Whitney U-test, the statistical significance of the results was assessed at a level of not less than 95% (risk of error not more than 5% - p <0.05). Results Infertile women with endometrioma and adenomyosis have lower AMH levels than infertile women with tubal factor. Among patients with endometriosis, there is an increase in serum FSH, LH, prolactin and estradiol compared with women without endometriosis. Dienogest moderately inhibits the secretion of FSH and LH; it has almost no effect on blood AMH and estradiol values. The use of dienogest can moderately increase the level of prolactin, It is noteworthy that these indicators are within the reference range. The use of diferelin for the treatment of endometriosis has a more active effect on the hormonal status of patients, given the decrease in such indicators as FSH and LH, AMH, estradiol and prolactin Conclusions. Women with infertility against the background of endometriosis have minor changes in the hypothalamic-pituitary-ovarian system, which indicates the need to develop medical measures in order to correct them. The use of dienogest compared to diferelin affects the hormonal status of patients with endometriosis to a lesser extent, given the pronounced anti-proliferative effect.